Evaluating the predictive effect of vitamin D on clinical outcomes of infliximab-treated Crohn’s disease patients - Zheng, Jiao; Gao, Hongping; Zhang, Yu; Sun, Mingxuan; Sun, Hang; Pei, Ying (Frontiers in Immunology, 2025)
BackgroundsThe aim of this study was to examine the clinical predictors of Infliximab (IFX) in Crohn’s disease (CD) patients in eastern China and to support further research on the vitamin D remission rate compared to CD patients.MethodsPatients with CD who were hospitalized at Xuzhou First People’s Hospital between January 2020 and December 2023 were included in our retrospective analysis. Clinical information was gathered from CD patients at baseline and the endpoint (7th IFX therapy, 38 weeks). To determine the baseline variable [Crohn’s Disease Activity Index (CDAI) < 150] for endpoint clinical remission in patients receiving IFX, and to examine the relationship between blood vitamin D (VIT-D) levels before starting IFX medication and CDAI at Week 38. The potential risk variables were then investigated using univariate, multivariate, and LASSO regression models.ResultsIncluded were 158 individuals with CD treated with IFX. At baseline, 18.35% of patients had a VIT-D deficit; 64.19% of patients experienced a decrease in VIT-D, and 63.29% of patients achieved clinical remission. The high Vitamin D levels at baseline were independent predictors of clinical remission after IFX therapy, according to univariate, multivariate, and LASSO regression analysis (P < 0.05). Receiver operating characteristic curve analysis revealed that AUC (95%CI) 0.56(0.25-0.95) was the endpoint CDAI (= 150) diagnostic value when the Vit-D level was 19.35 ng/ml. The corresponding sensitivity and specificity were 75.02% and 79.6%. Endpoint CDAI was independently predicted by male sex, age, BMI, and VIT-D levels <30 ng/ml (P < 0.05).ConclusionAfter receiving IFX therapy, CD patients in eastern China with higher VIT-D levels were more likely to achieve clinical remission, particularly those who were male, older, had a higher BMI, and had VIT-D levels below 30 ng/ml.